2021
DOI: 10.4269/ajtmh.20-1043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personalized Support at Home on the Prevalence of Anemia in Pregnancy in Burkina Faso: A Cluster Randomized Trial

Abstract: Burkina Faso has high prevalence of anemia in pregnancy (hemoglobin < 11 g/dL), despite the implementation of the WHO recommended guidelines. This study aimed to test the effects of personalized support for pregnant women at home on the trend of anemia prevalence in pregnancy. A cluster randomized trial was conducted from January 2015 to August 2016 at Sindou health district in Burkina Faso. Data were collected from 617 women in their first or second trimester of pregnancy, including 440 and 177 women in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Initial research demonstrated that individualized home-based support for pregnant women, with an emphasis on nutritional counseling, iron supplementation, malaria and intestinal parasitosis prevention, in conjunction with proper antenatal care, reduced the prevalence of anemia in pregnancy. 11 Compared to the control group, the intervention group had greater proportions of preterm or low birth weight births and decreased abortion rates; nevertheless, the adjusted frequency differences between the two groups were not statistically significant. Alternatively, there was a modest decline in stillbirths.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Initial research demonstrated that individualized home-based support for pregnant women, with an emphasis on nutritional counseling, iron supplementation, malaria and intestinal parasitosis prevention, in conjunction with proper antenatal care, reduced the prevalence of anemia in pregnancy. 11 Compared to the control group, the intervention group had greater proportions of preterm or low birth weight births and decreased abortion rates; nevertheless, the adjusted frequency differences between the two groups were not statistically significant. Alternatively, there was a modest decline in stillbirths.…”
Section: Discussionmentioning
confidence: 78%
“…The relative increase in the frequency of low birth weight in the intervention group may be attributable to the rise in this group's hemoglobin levels. 11 In fact, according to some writers, iron supplementation of non-anemic pregnant women is related with low birth weight, although this association remains controversial. 20 Other writers have claimed, contrary to ours, that measures to reduce low birth weight should be undertaken before or very early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations